Strategy on implementing genetic algorithm on FPGA for polarization control application - Esmaeilian-Marnani, Aida; Mamdoohi, Ghazaleh; Abas, Ahmad Fauzi; Samsudin, Khairulmizam; Hidayat, Ariya; Ibrahim, Noor Hisham (IEEE, 2010)
This electronic document is a “live” template. The various components of your paper [title, text, heads, etc.] are already defined on the style sheet, as illustrated by the portions given in this document.